Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.5194/amt-6-1425-2013
|View full text |Cite
|
Sign up to set email alerts
|

On the interference of Kr during carbon isotope analysis of methane using continuous-flow combustion–isotope ratio mass spectrometry

Abstract: Stable carbon isotope analysis of methane (δ13C of CH4) on atmospheric samples is one key method to constrain the current and past atmospheric CH4 budget. A frequently applied measurement technique is gas chromatography (GC) isotope ratio mass spectrometry (IRMS) coupled to a combustion-preconcentration unit. This report shows that the atmospheric trace gas krypton (Kr) can severely interfere during the mass spectrometric measurement, leading to significant biases in &del… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 60 publications
6
44
0
Order By: Relevance
“…Thus the δ 13 C-CH 4 measurements on a GC-IRMS system can be biased if Kr is not sufficiently separated either from CH 4 or from the CH 4 -derived CO 2 peak after the CH 4 combustion. Schmitt et al (2013) demonstrated that the doubly charged krypton isotope 86 Kr 2+ , produced in the ion source of an IRMS, can cause lateral tailing extending into the Faraday cups used for δ 13 C analysis (i.e. m/z of 44, 45 and 46), which compromises the measured signal of the CH 4 -derived CO 2 peak.…”
Section: Krypton Interference In Gc-irmsmentioning
confidence: 99%
“…Thus the δ 13 C-CH 4 measurements on a GC-IRMS system can be biased if Kr is not sufficiently separated either from CH 4 or from the CH 4 -derived CO 2 peak after the CH 4 combustion. Schmitt et al (2013) demonstrated that the doubly charged krypton isotope 86 Kr 2+ , produced in the ion source of an IRMS, can cause lateral tailing extending into the Faraday cups used for δ 13 C analysis (i.e. m/z of 44, 45 and 46), which compromises the measured signal of the CH 4 -derived CO 2 peak.…”
Section: Krypton Interference In Gc-irmsmentioning
confidence: 99%
“…Both values were measured before the awareness of the Kr issue. According to Schmitt et al (2013) , thus close to our value of −48.03 ‰ (Table 4). Further validation of the Kr-corrected data recently published by Möller et al (2013) is provided by new measurements for the same time period using our new set-up and samples from the TALDICE core.…”
Section: Intercomparisonmentioning
confidence: 75%
“…Our IsoPrime is equipped with a universal triple collector plus two additional cups to monitor m/z 28 and 32, named N 2 -cup and O 2 -cup, respectively; details are described in Schmitt et al (2013). This cup configuration allows for various source settings to analyse gas species of up to m/z 85 and, coincidentally, isotope analysis of doubly charged Xe isotopes.…”
Section: Continuous-flow Irmsmentioning
confidence: 99%
“…Our system includes permanent oxidation, a post-combustion cryo-trap and a second GC column, similar to Melton et al (2011b). This GC-C-GC-IRMS method ensures a stable oxidation of the combustion reactor with minimized oxygen load into the IRMS, and it excludes interferences of the δ 13 C-CH 4 measurement with Kr inside the IRMS (Schmitt et al, 2013). The system is anchored to the international isotope scales using reference gases that were synthesized after for δ 13 C-CH 4 or calibrated by intercomparison measurements with two external laboratories for δ 15 N-N 2 O and δ 18 O-N 2 O.…”
Section: P Sperlich Et Al: Ch 4 and N 2 O Isotopes In Ice Core Samplesmentioning
confidence: 99%
“…Krypton -which is abundant in the atmosphere at ∼ 1 ppm (Aoki and Makide, 2005) -was found to co-elute from the GC column with CH 4 and interfere with the analysis of CH 4 -derived CO 2 (Schmitt et al, 2013). The system described here deploys a post-combustion cryo-trap followed by a second GC column (Fig.…”
Section: Excluding Krypton Interferencementioning
confidence: 99%